EFEKTIVITAS SISTEM PENGADAAN SECARA ELEKTRONIK (SPSE) ATAS BARANG DAN JASA DI KABUPATEN BANJARNEGARA - Peni Yulia Astuti (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2017)
One of e-government services that were adopted by the Government District Banjarnegara is Procurement of Goods/Services in Electronics (LPSE) in order to fix some of the weaknesses of the procurement of government goods/ services are carried out manually. This study aims to assess and analyze the effectiveness of Electronic Procurement System (SPSE) in the Procurement of Goods/Services in the District Banjarnegara. The study was conducted at the office of the District LPSE Banjarnegara, this study uses the effectiveness of Electronic Procurement System (SPSE) in the Procurement of Goods/Services in the District Banjarnegara. Data were obtained through interviews with informants related to the implementation of the Electronic Procurement System (SPSE) In District Banjarnegara and conduct research on a data source in the form of archives, documents, statistical data, and other important texts related to the research. The analysis was performed in 3 (three) using the stages: data reduction, data presentation and conclusion Manufacture, Verification, and Reflection The results showed that the application of LPSE in the district. Banjarnegara has increased transparency in the procurement of government goods/services 5 (five) assessment indicators, namely Production, Efficiency, Satisfaction, excellence, and development to assess the extent of the effectiveness of the implementation of the SPSE in the district. Banjarnegara which already shows a fairly good category/ quite effective.